Subsidy distribution among the subjects of agro-industrial complex in Kazakhstan - S. K. Seitov (Аграрная наука Евро-Северо-Востока, 2023)
The problem of limited budget funds for subsidizing agriculture is acute in Kazakhstan. Under these conditions, it is important to ensure targeting of subsidies, when they are delivered to those producers who are able to use them effectively for the production needs. The aim of the research is to highlight the main trends in the distribution of subsidies in the agro-industrial complex of Kazakhstan and their impact on the results of the industry. The efficiency of subsidies is influenced not only by their structure by type, but also by their distribution among commodity producers. On average in 2018-2021, thirty largest subjects of the agro-industrial complex, receiving 4-10 % of the total amount of subsidies, give 4-15 % of tax revenues, have 3-7 % of the gross profit in agriculture in Kazakhstan. The concentration ratios for 2018-2021 do not exceed 0.10, and for 150 largest farms they do not exceed 0.21, showing no significant changes in 2020-2021. This indicator allows to estimate the degree of uneven distribution of subsidies among recipient farms: the higher it is, the more unevenly the support is distributed. The indices of even distribution of subsidies based on profits are characterized by a downward trend in 2018-2021, regarding that the contribution of the largest subsidy recipients to the total gross profit has decreased. The same suspicious trend is inherent in the Equal Distribution of Subsidies Indices based on taxes paid. Based on the author’s method, the paper reveals the connection between production efficiency, provided at the expense of innovations, and the increase in the contribution of innovatively active producers to the industry's gross profit. By subsidizing advanced and innovatively active producers, the state will contribute to the increase of return on subsidies (expressed as an increase in the recipients' contribution to the industry’s gross profit). Based on these principles, the author recommends to prioritize subsidizing among subjects of the agro-industrial complex.